Acid-resistant composite membrane as well as preparation method and application thereof in acid purification
Through the combination technology of copolymer A and PTFE base film, an acid-resistant composite film was prepared, which solved the problem of low corrosion and interception efficiency of traditional films in an acid environment, and achieved efficient acid purification and impurity removal.
Patent Information
- Application Number
- CN202411841495.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to develop acid-resistant composite films in an acid environment, resulting in corrosion of the membrane material and damage to the physical structure, affecting the separation performance, and the traditional separation membrane has a low interception efficiency of acid ions and metal ions.
Perfluoro-2-methylene-4-methyl-1,3-dioxolane was used to copolymerize with chloroethylene trifluoroethylene to prepare copolymer A, and mix it with acetone in a perfluoro solvent to form a composite layer film liquid, coated on the PTFE base film, and prepare an acid-resistant composite film.
The prepared acid-resistant composite membrane is used for a long time in a high concentration of acidic environment, has excellent filtration performance, can effectively remove impurities in acid, achieve acid purification, and remove acid ions and metal ions to level E2.
Smart Images

Figure CN119607895A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid separation membranes, and particularly relates to an acid-resistant composite membrane and a preparation method thereof and application thereof in the purification of various acids. Background Art
[0002] In many industrial fields, acids are indispensable and important chemicals. For example, in the metal finishing industry, strong inorganic acids (such as sulfuric acid, nitric acid, and hydrochloric acid) are widely used to remove oxides from the metal surface. This process is called pickling. Pickling can effectively reduce the impact of oxides on the metal surface on subsequent production operations and improve product quality. In steel production, pickling is a key process that can make the steel surface smoother and cleaner for subsequent processing, such as coating and plating. In the electronics industry, acids are also used in processes such as etching. For example, in the semiconductor manufacturing process, acids such as hydrofluoric acid are used to etch silicon wafers to create precise circuit patterns. In the chemical synthesis industry, acids often participate in chemical reactions as catalysts or reactants. For example, sulfuric acid plays the role of a catalyst in many organic synthesis reactions. With the continuous development of industry, the purity requirements for acids are getting higher and higher, and at the same time, higher requirements are also placed on the recovery and reuse of acids. Traditional acid purification methods have many limitations. For example, physical methods such as distillation to purify acids often consume a lot of energy, and for some high-boiling point acids or acids with boiling points close to those of impurities, the distillation effect is not ideal. Although the chemical precipitation method can remove certain metal ion impurities in the acid, it will introduce new chemical substances, which may affect the subsequent use of the acid. In addition, for some complex impurity systems, the treatment effect of the chemical precipitation method is limited.
[0003] In this context, liquid separation membrane technology has gradually become a research hotspot, and the development and application of acid-resistant membranes has always been an important research direction. However, ordinary membrane materials are often easily corroded in acid environments, and their chemical structures are prone to degradation reactions, which leads to the destruction of the physical structure of the membrane, the damage and thinning of the membrane, etc., which directly affect the performance of the separation membrane and make it lose its original separation function. On the other hand, traditional separation membranes are also insufficient in the interception effect of acid ions and metal ions. In high-acid solutions, the presence of acid ions and metal ions is relatively common, and due to the limitations of their structure and material properties, traditional separation membranes have low interception efficiency for these acid ions and metal ions, and cannot effectively separate acid ions and metal ions from acid solutions. Therefore, it is particularly important to develop an acid-resistant composite membrane. This acid-resistant composite membrane must not only be able to withstand acid corrosion, but also have good separation performance, can effectively remove impurities in the acid, and achieve acid purification. By preparing an acid-resistant composite membrane, a new and efficient solution can be provided for the purification of acids, which has great potential in reducing production costs, improving product quality, and reducing environmental pollution. Summary of the invention
[0004] In view of the above problems, the present invention provides an acid-resistant composite membrane and a preparation method thereof and application in acid purification. The acid-resistant composite membrane used is a composite membrane material that can be used for a long time in a high-concentration acid environment and has excellent filtration performance.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A method for preparing an acid-resistant composite film comprises the following steps:
[0007] (1) Preparation of copolymer A:
[0008] Perfluoro-2-methylene-4-methyl-1,3-dioxolane (CAS No. 17256-52-9) and chlorotrifluoroethylene are mixed in a perfluoro solvent and polymerized under the action of a catalyst to obtain a copolymer A;
[0009] (2) Preparation of acid-resistant composite film:
[0010] The copolymer A and acetone are mixed in a perfluorinated solvent at 60-80° C. to obtain a composite layer membrane liquid, and then the composite layer membrane liquid is coated on the surface of a polytetrafluoroethylene-based membrane, and dried to obtain the acid-resistant composite membrane.
[0011] Preferably, the perfluoro solvent is selected from one or more of Fluorinert FC-40, Fluorinert FC-72 or Fluorinert FC-75.
[0012] Preferably, the mass ratio of the perfluoro-2-methylene-4-methyl-1,3-dioxolane to the chlorotrifluoroethylene in step (1) is 1:5-7.
[0013] Preferably, in step (1), the total mass concentration of perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene in the perfluoro solvent is 30% to 40%.
[0014] Preferably, the mixing in step (1) is carried out at 40-65°C.
[0015] Preferably, the catalyst in step (1) is perfluoropropionyl peroxide.
[0016] Preferably, the amount of the catalyst added in step (1) is 0.01% to 0.02% of the mass of the perfluoro-2-methylene-4-methyl-1,3-dioxolane.
[0017] Preferably, step (1) further comprises a step of removing the solvent after the polymerization reaction.
[0018] Preferably, in step (2), the mass concentration of the copolymer A in the composite layer membrane solution is 0.05% to 0.2%.
[0019] Preferably, the amount of acetone added in step (2) is 2.5% of the mass of the perfluoro solvent.
[0020] Preferably, the polytetrafluoroethylene-based membrane in step (2) is prepared by hot pressing polyphenylene sulfide (PPS) non-woven fabric and polytetrafluoroethylene (PTFE).
[0021] Preferably, the pore size of the basement membrane in step (2) is 10-15 nm.
[0022] Preferably, the perfluoro-2-methylene-4-methyl-1,3-dioxolane described in step (1) is prepared by the following method:
[0023] (0-1) 2-chloro-1-propanol, 1-chloro-2-propanol and methyl trifluoropyruvate are mixed for reaction, and then DMSO and sodium carbonate are added. The reaction mixture is then poured into water, and the organic phase is extracted with an extractant, and then dried and fractionated under reduced pressure to obtain 2-methylcarbomethoxy-2-trifluoromethyl-4-methyl-1,3-dioxolane;
[0024] (0-2) dissolving 2-methoxy-2-trifluoromethyl-4-methyl-1,3-dioxolane in 1,1,2-trichlorotrifluoroethane (R113), then adding a KOH aqueous solution until it becomes slightly alkaline, drying under reduced pressure, adding an excess of a hydrochloric acid solution, separating the layers, separating the organic layer and performing reduced pressure distillation to obtain perfluoro-2,4-dimethyl-1,3-dioxolane-2-carboxylic acid;
[0025] (0-3) Perfluoro-2,4-dimethyl-1,3-dioxolane-2-carboxylic acid was added to an excess of NaOH, followed by vacuum drying, decomposition in a nitrogen atmosphere at 250-280°C, and collection in a -78°C cold trap to obtain perfluoro-2-methylene-4-methyl-1,3-dioxolane.
[0026] Preferably, in step (0-1), the molar ratio of 2-chloro-1-propanol, 1-chloro-2-propanol and methyl trifluoropyruvate is 1:1:1.
[0027] Preferably, the reaction in step (0-1) is carried out in a cold water bath.
[0028] The second object of the present invention is to provide an acid-resistant composite film obtained by the above preparation method.
[0029] The second object of the present invention is to provide the use of the acid-resistant composite membrane obtained by the above preparation method in acid purification.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention selects perfluoro-2-methylene-4-methyl-1,3-dioxolane and trifluorochloroethylene as the main components, and optimizes the ratio to ensure the ideal properties of copolymer A. The polymer chain contains multiple fluorine atoms and trifluorochloroethylene units, which give the membrane good chemical stability, especially the ability to resist degradation in a strong acid environment. The introduction of the catalyst perfluoropropionyl peroxide further improves the polymerization reaction efficiency and the stability of the copolymer.
[0032] (2) Fluorinert series perfluorinated solvents (FC-40, FC-72, FC-75) are used as reaction and dissolution media to ensure the chemical inertness and dissolution capacity of the reaction process, effectively avoid the introduction of impurities during the polymerization reaction, ensure the purity and performance of copolymer A, help form a uniform membrane liquid, and facilitate the membrane coating process. At the same time, adding acetone for heating and stirring can effectively improve the uniformity and stability of the composite layer membrane liquid, significantly improve the film-forming property and adhesion of the membrane liquid, and make the final composite membrane have better density and mechanical properties.
[0033] (3) The PTFE base membrane is made of polyphenylene sulfide non-woven fabric and polytetrafluoroethylene by hot pressing. The introduction of PPS non-woven fabric gives the base membrane good mechanical strength and chemical stability, while the PTFE layer provides excellent acid resistance. This ensures the base membrane's tolerance in a highly acidic environment and improves the overall performance and service life of the membrane.
[0034] (4) The acid-resistant composite membrane can be used for a long time in electronic-grade hydrofluoric acid, nitric acid and hydrochloric acid without significant changes in physical properties and chemical stability. At the same time, after treating industrial-grade acid, the membrane can remove acid radical ions and metal ions up to E2 level, showing excellent filtration effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 These are the appearance pictures of each membrane in the test example before and after being immersed in hydrofluoric acid for 7 days.
[0036] Figure 2 This is a comparison chart of the stability performance of the diaphragm of Example 2 in the test example after long-term immersion in hydrofluoric acid. DETAILED DESCRIPTION
[0037] Example 1
[0038] (1) Synthesis of perfluoro-2-methylene-4-methyl-1,3-dioxolane:
[0039] Add 2-chloro-1-propanol, 1-chloro-2-propanol, and methyl trifluoropyruvate to a three-necked flask in a ratio of 1:1:1 and stir for 4 hours in a cold water bath (15°C). Then add appropriate amounts of DMSO and sodium carbonate, and after stirring evenly, pour the resulting mixture into 20°C water, extract the organic phase with dichloromethane, dry with zinc sulfate, and decompress and split to obtain product a (2-methyl-2-trifluoromethyl-4-methyl-1,3-dioxolane). Add product a and 1,1,2-trichlorotrifluoroethane (R113) to a three-necked flask in a ratio of 1:5, dissolve product a in 1,1,2-trichlorotrifluoroethane (R113), stir evenly, add NaOH aqueous solution to adjust the mixed solution to slightly alkaline, dry under reduced pressure, add excess nitric acid solution to the obtained solid product, separate the liquids, separate the organic layer and perform reduced pressure distillation to obtain product b (perfluoro-2,4-dimethyl-1,3-dioxolane-2-carboxylic acid). Add product b to excess NaOH and stir evenly, then vacuum dry at 70°C, decompose in a nitrogen atmosphere at 280°C, and then collect with a -78°C cold trap to obtain perfluoro-2-methylene-4-methyl-1,3-dioxolane.
[0040] (2) Synthesis of copolymer A:
[0041] Perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene are added to a perfluoro solvent in a ratio of 1:5. The perfluoro solvent used is Fluorinert FC-40, and the sum of the mass concentrations of perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene is 30%.
[0042] Heat and stir at 40°C to ensure that the raw materials are fully mixed and dissolved, and then add the catalyst perfluoropropionyl peroxide, the added mass of which is 0.01% of the mass of perfluoro-2-methylene-4-methyl-1,3-dioxolane. Then carry out a polymerization reaction, and after removing the solvent by evaporation, obtain copolymer A.
[0043] (3) Preparation of composite membrane solution:
[0044] The prepared copolymer A was dissolved in the perfluoro solvent Fluorinert FC-40, so that the mass concentration of copolymer A was 0.05%. The perfluoro solvent was able to dissolve the copolymer A well during the dissolution process, ensuring the uniformity and stability of the composite layer membrane liquid. Subsequently, acetone with a mass of 2.5% of the mass of the perfluoro solvent was added to the solution, and heated and stirred at 60°C for 12 hours to form a composite layer membrane liquid.
[0045] (4) Preparation of acid-resistant composite film:
[0046] The prepared composite layer membrane liquid was coated on the surface of the PTFE base membrane and dried at 60°C for 8 hours to obtain an acid-resistant composite membrane. The PTFE base membrane was prepared by hot pressing polyphenylene sulfide (PPS) non-woven fabric and polytetrafluoroethylene (PTFE), and the pore size of the base membrane was 10 nm.
[0047] Example 2
[0048] (1) Synthesis of perfluoro-2-methylene-4-methyl-1,3-dioxolane:
[0049] Add 2-chloro-1-propanol, 1-chloro-2-propanol, and methyl trifluoropyruvate to a three-necked flask in a ratio of 1:1:1 and stir for 4 hours in a cold water bath (15°C). Then add appropriate amounts of DMSO and sodium carbonate, and after stirring evenly, pour the resulting mixture into 20°C water, extract the organic phase with dichloromethane, dry with zinc sulfate, and decompress and split to obtain product a (2-methyl-2-trifluoromethyl-4-methyl-1,3-dioxolane). Add product a and 1,1,2-trichlorotrifluoroethane (R113) to a three-necked flask in a ratio of 1:5, dissolve product a in 1,1,2-trichlorotrifluoroethane (R113), stir evenly, add NaOH aqueous solution to adjust the mixed solution to slightly alkaline, dry under reduced pressure, add excess nitric acid solution to the obtained solid product, separate the liquids, separate the organic layer and perform reduced pressure distillation to obtain product b (perfluoro-2,4-dimethyl-1,3-dioxolane-2-carboxylic acid). Add product b to excess NaOH and stir evenly, then vacuum dry at 70°C, decompose in a nitrogen atmosphere at 280°C, and then collect with a -78°C cold trap to obtain perfluoro-2-methylene-4-methyl-1,3-dioxolane.
[0050] (2) Synthesis of copolymer A:
[0051] Perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene are added to a perfluoro solvent in a ratio of 1:6. The perfluoro solvent used is Fluorinert FC-72. The total mass concentration of perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene is 35%.
[0052] The mixture was heated and stirred at 60°C to ensure that the raw materials were fully mixed and dissolved, and then the catalyst perfluoropropionyl peroxide was added, the added mass of which was 0.015% of the mass of perfluoro-2-methylene-4-methyl-1,3-dioxolane. A polymerization reaction was then carried out, and the solvent was removed by evaporation to obtain copolymer A.
[0053] (3) Preparation of composite membrane solution:
[0054] The prepared copolymer A was dissolved in a perfluoro solvent so that the mass concentration of the copolymer A was 0.18%. The perfluoro solvent was able to dissolve the copolymer A well during the dissolution process, ensuring the uniformity and stability of the composite membrane liquid. Subsequently, acetone of 2.5% of the mass of the perfluoro solvent was added to the solution, and the mixture was heated and stirred at 80°C for 20 hours to form a composite membrane liquid.
[0055] (4) Preparation of acid-resistant composite film:
[0056] The prepared composite layer membrane liquid was coated on the surface of the PTFE base membrane and dried at 80°C for 11 hours to obtain an acid-resistant composite membrane. The PTFE base membrane was prepared by hot pressing polyphenylene sulfide (PPS) non-woven fabric and polytetrafluoroethylene (PTFE), and the pore size of the base membrane was 14 nm.
[0057] Example 3
[0058] (1) Synthesis of perfluoro-2-methylene-4-methyl-1,3-dioxolane:
[0059] Add 2-chloro-1-propanol, 1-chloro-2-propanol, and methyl trifluoropyruvate to a three-necked flask in a ratio of 1:1:1 and stir for 4 hours in a cold water bath (15°C). Then add appropriate amounts of DMSO and sodium carbonate, and after stirring evenly, pour the resulting mixture into 20°C water, extract the organic phase with dichloromethane, dry with zinc sulfate, and decompress and split to obtain product a (2-methyl-2-trifluoromethyl-4-methyl-1,3-dioxolane). Add product a and 1,1,2-trichlorotrifluoroethane (R113) to a three-necked flask in a ratio of 1:5, dissolve product a in 1,1,2-trichlorotrifluoroethane (R113), stir evenly, add NaOH aqueous solution to adjust the mixed solution to slightly alkaline, dry under reduced pressure, add excess nitric acid solution to the obtained solid product, separate the liquids, separate the organic layer and perform reduced pressure distillation to obtain product b (perfluoro-2,4-dimethyl-1,3-dioxolane-2-carboxylic acid). Add product b to excess NaOH and stir evenly, then vacuum dry at 70°C, decompose in a nitrogen atmosphere at 280°C, and then collect with a -78°C cold trap to obtain perfluoro-2-methylene-4-methyl-1,3-dioxolane.
[0060] (2) Synthesis of copolymer A:
[0061] Perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene are added to a perfluoro solvent in a ratio of 1:7. The perfluoro solvent used is Fluorinert FC-75. The total mass concentration of perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene is 40%.
[0062] The mixture was heated and stirred at 65°C to ensure that the raw materials were fully mixed and dissolved, and then the catalyst perfluoropropionyl peroxide was added, the added mass of which was 0.02% of the mass of perfluoro-2-methylene-4-methyl-1,3-dioxolane. A polymerization reaction was then carried out, and the solvent was removed by evaporation to obtain copolymer A.
[0063] (3) Preparation of composite membrane solution:
[0064] The prepared copolymer A was dissolved in a perfluoro solvent so that the mass concentration of the copolymer A was 0.2%. The perfluoro solvent was able to dissolve the copolymer A well during the dissolution process, ensuring the uniformity and stability of the composite membrane liquid. Subsequently, acetone of 2.5% of the mass of the perfluoro solvent was added to the solution, and the mixture was heated and stirred at 80°C for 24 hours to form a composite membrane liquid.
[0065] (4) Preparation of acid-resistant composite film:
[0066] The prepared composite layer membrane liquid was coated on the surface of the PTFE base membrane and dried at 80°C for 12 hours to obtain an acid-resistant composite membrane. The PTFE base membrane was prepared by hot pressing polyphenylene sulfide (PPS) non-woven fabric and polytetrafluoroethylene (PTFE), and the pore size of the base membrane was 15 nm.
[0067] Comparative Example
[0068] As a comparison, trifluorochloroethylene and perfluoro(alkyl vinyl ether) were used to synthesize a perfluoro copolymer, specifically using the following method:
[0069] (1) Synthesis of copolymer B:
[0070] Perfluoro(alkyl vinyl ether) and chlorotrifluoroethylene are mixed in a perfluoro solvent, wherein the perfluoro solvent used is Fluorinert FC-72, and a polymerization reaction is carried out under the action of a catalyst to obtain a copolymer B; wherein the catalyst is perfluoropropionyl peroxide;
[0071] (2) Preparation of composite membrane solution:
[0072] The prepared copolymer B was dissolved in a perfluoro solvent to make the mass concentration of copolymer B 0.2%. The perfluoro solvent was able to dissolve copolymer B well during the dissolution process, ensuring the uniformity and stability of the composite membrane liquid. Subsequently, acetone with a mass of 2.5% of the mass of the perfluoro solvent was added to the solution, and heated and stirred at 80°C for 24 hours to form a composite membrane liquid.
[0073] (3) Preparation of acid-resistant composite film:
[0074] The prepared composite layer membrane liquid was coated on the surface of the PTFE base membrane and dried at 80°C for 12 hours to obtain an acid-resistant composite membrane. The PTFE base membrane was prepared by hot pressing polyphenylene sulfide (PPS) non-woven fabric and polytetrafluoroethylene (PTFE), and the pore size of the base membrane was 15 nm.
[0075] Performance Test:
[0076] (1) Diaphragm immersion in hydrofluoric acid stability test:
[0077] The conventional PDMS membrane, the membrane of Example 1, the membrane of Example 2, the membrane of Example 3, and the comparative example membrane were immersed in a solution with a hydrofluoric acid content of 50%. After immersion for 7 days, the state of the membrane was as follows: Figure 1 shown.
[0078] Depend on Figure 1 It can be seen that the conventional PDMS membrane has a membrane separation phenomenon after being immersed in a hydrofluoric acid solution. The reason is that the strong acid environment causes the bonding force between the PDMS, the base membrane and the non-woven fabric to decrease. The membranes of the other four embodiments all have a membrane separation phenomenon, indicating that the membranes of the four embodiments have strong acid resistance.
[0079] (2) Analysis and testing of hydrofluoric acid waste liquid products after membrane filtration:
[0080] The hydrofluoric acid waste liquid was subjected to membrane separation tests using the four membranes of Example 1, Example 2, Example 3, and the comparative example, respectively. The membrane separation device was a homemade small-scale special membrane filtration component with an operating pressure of 0.6 MPa. The ion components of the raw material and the permeate after membrane separation were analyzed to evaluate the membrane separation performance. The test results are shown in Table 1.
[0081] Table 1 Analysis results of electronic grade hydrofluoric acid products
[0082] index E2 E3 raw material Example 1 Example 2 Example 3 Comparative Example Hydrofluoric acid content (%) ≥40.0 ≥40.0 38 38.2 38.8 38.5 38.1 Particles (≥0.5μm) pcs / mL ≤50 ≤25 300 48 36 39 100 Particles (≥1.0μm) pcs / mL ≤25 ≤10 200 23 16 20 66 <![CDATA[Fluorosilicate (SiF4 2- ) mg / kg]]> ≤50 ≤50 1580 75 49 69 520 <![CDATA[Nitrate (NO3 - ) mg / kg]]> ≤3 ≤3 59 20 3 9 41 <![CDATA[Sulfate (SO4 2- ) mg / kg]]> ≤5 ≤0.5 68 18 3 6 46 <![CDATA[Phosphate (PO4 3- ) mg / kg]]> ≤1 ≤0.5 58 29 0.8 6.3 37 Zinc (Zn) μg / kg ≤50 ≤10 293 100 35 66 239
[0083] From the data in Table 1, it can be seen that after filtration with the perfluorinated membrane, the hydrofluoric acid waste liquid can have a certain filtering and impurity removal performance, and the permeate of the membrane of Example 2 can reach the E2 level. However, the filtering effect of the comparative membrane is not ideal. Although the comparative membrane has strong acid resistance, its performance as a filtering and separation membrane for waste acid recovery and separation filtration is poor.
[0084] (3) Diaphragm long-term stability test:
[0085] According to the data in Table 1, it can be seen that the performance of the membrane of Example 2 is relatively good. Therefore, the perfluorinated membrane of Example 2 is selected for long-term stability test. The above-mentioned raw material hydrofluoric acid waste liquid is selected as the filtration test liquid. The membrane of Example 2 is immersed in a solution with a hydrofluoric acid concentration of 50%. The membrane is taken out for filtration test on the 0th day, the 1st day, the 7th day, the 14th day, the 21st day, and the 28th day of immersion to determine the stability of the membrane after immersion in high-concentration hydrofluoric acid solution. The test results are as follows: Figure 2 shown.
[0086] according to Figure 2 The results show that the membrane of Example 2 still has a good filtering effect on the hydrofluoric acid solution after being immersed in a high concentration hydrofluoric acid solution, and this acid-resistant perfluorinated membrane has good stability.
[0087] The above table is for illustrating the components contained in hydrofluoric acid, and the content of the components is closely related to the source, but does not limit the applicability of the invention. The hydrofluoric acid product purified and recovered by the method meets the electronic grade reuse standard.
[0088] The acid-resistant composite membrane of the present invention is widely used in filtering and separation devices in the chemical, metallurgical, electronic and other industrial fields. It is particularly suitable for liquid filtration in highly acidic environments, various waste acid treatments, and the preparation and purification of high-purity chemicals. Through actual application tests, the membrane exhibits excellent acid resistance and high-efficiency filtration performance, greatly improving the safety and efficiency in industrial production.
[0089] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. A method for preparing an acid-resistant composite film, characterized in that: The steps include: (1) Preparation of copolymer A: Perfluoro-2-methylene-4-methyl-1,3-dioxolane and chlorotrifluoroethylene are mixed in a perfluoro solvent and subjected to polymerization reaction under the action of a catalyst to obtain a copolymer A; the catalyst is perfluoropropionyl peroxide; (2) Preparation of acid-resistant composite film: The copolymer A and acetone are mixed in a perfluorinated solvent at 60-80° C. to obtain a composite layer membrane liquid, and then the composite layer membrane liquid is coated on the surface of a polytetrafluoroethylene-based membrane, and dried to obtain the acid-resistant composite membrane.
2. The preparation method according to claim 1, characterized in that The perfluorinated solvent is selected from one or more of Fluorinert FC-40, Fluorinert FC-72 and Fluorinert FC-75.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the perfluoro-2-methylene-4-methyl-1,3-dioxolane to the chlorotrifluoroethylene in step (1) is 1:5-7.
4. The preparation method according to claim 1, characterized in that: The mixing in step (1) is carried out at 40-65°C.
5. The preparation method according to claim 1, characterized in that: The amount of the catalyst added in step (1) is 0.01% to 0.02% of the mass of the perfluoro-2-methylene-4-methyl-1,3-dioxolane.
6. The preparation method according to claim 1, characterized in that: In step (2), the mass concentration of the copolymer A in the composite layer membrane solution is 0.05% to 0.2%.
7. The preparation method according to claim 1, characterized in that: The amount of acetone added in step (2) is 2.5% of the mass of the perfluoro solvent.
8. The preparation method according to claim 1, characterized in that: The polytetrafluoroethylene-based membrane described in step (2) is prepared by hot pressing polyphenylene sulfide non-woven fabric and polytetrafluoroethylene.
9. The second object of the present invention is to provide an acid-resistant composite film obtained by the above preparation method.
10. The second object of the present invention is to provide the use of the acid-resistant composite membrane obtained by the above preparation method in acid purification.
Citation Information
Cited By
A device system and method for resourceful treatment of photovoltaic fluorine-containing mixed acid wastewater
CN122771584A